Scattering and dynamics of polymers : seeking order in disordered systems - Han, Charles C.; Akcasu, Ziyaeddin A. (Singapore : John Wiley & Sons, 2011)
'In this book, we will start from the traditional light scattering for dilute solution, and then bring in the concepts of fluctuations, correlations, and also space-time correlation function'--
Includes bibliographical references and index.
Keywords: Light -- scattering; Polymers -- Spectra; Polymers -- Rheology